A Short History of Transport in Japan: From Ancient Times to the Present - John Andrew Black (Open Book Publishers, 2022)
"A Short History of Transport in Japan from Ancient Times to the Present is a unique study: the first by a Western scholar to place the long-term development of Japanese infrastructure alongside an analysis of its evolving political economy. Drawing from New Institutional Economics, Black offers an historically informed critique of contemporary planning using the example of Japan's historical institutions, their particular biases, and the power they have exerted over national and local transport, to identify how reformed institutional arrangements might develop more sustainable and equitable transport services. With chapters addressing each major form of transport, Black examines the predominant role of institutions and individuals - from seventeenth-century shoguns to post-war planners - in transforming Japan's maritime infrastructure, its roads and waterways, and its adoption of rail and air transport. Using a multidisciplinary, comparative, and chronological approach, the book consults a range of technical, cultural, and political sources to tease out these interactions between society and technology. This spirited new contribution to transport studies will attract readers interested in institutional power, the history of transport, and the development of future infrastructure, as well as those with a general interest in Japan."–Publisher's website
Keywords: 330; air transport; history; Japan; maritime infrastructure; New Institutional Economics; planning; political economy; rail; roads; society; technology; transport